Atividade enzimática, população e análise de dna da biodiversidade microbiana do solo em agroecossistemas do semi-árido - Oliveira, Virgínia Carla de (2004)
the society is highly concerned on life quality, mostly in terms of environment and health. The environmental issues are emergencial in the social agenda to the extent that the human being exploitis the natural resources beyond its regenerative capacity. In this context, the soil biodiversity may constitute an excellent indicator to monitor environmental shifts. In ecosystems such as the Caatinga biome, the major one in the Brazilian Semi-arid Region, the deforestation and the forest fires are still common practices for land farming preparation. This current research investigated the effect of agricultural practices on the soil microbial community, in an agro-ecological dairy system developed for small stockholder farms within the Caatinga biome of N. Sr.ª da Glória-SE. For this purpose, some parameters were used such as enzymatic activity, total microbial population and the DNA analysis of the soil microbial community. These microbial bioindicators were applied to four agro-forestry-pasture systems: reforested areas with the tree legume sabiá (Mimosa caesalpiniaefolia ); pastures of grass (Urocloa moçambisensis); pastures of Gliricidia sepium; palm crop (Opuntia ficus indica), cultivated in adensed rows; and undisturbed native Caatinga grassland, used as control. For the determination of the total soil microbial activity, the hydrolysis of fluorescein diacetate (FDA) method was used. For the determination of the total microbial population it was used the soil dilution technique in to plates containing selective culture media for fungi, bacteria and actinomycetes. The molecular microbial profile was determined by the Amplified Ribosomal DNA Restriction Analysis (ARDRA), extracting the DNA directly from soil and amplifing ribosomal DNA from fungi and bacteria in a polimerase reaction (PCR). The hydrolysis of FDA indicates microbial activity in all agro-forestry-pasture systems. The highest microbiological activity was found in soil under Gliricidia sepium: 0,605 g FDA hydrolyzed min-1 g-1 soil. The total microbial population, indicated that the soil under the palm crop harbours the highest fungi and actinomycete populations: 21 e 127 ufc x 10g/soil, respectively. The highest soil bacteria population, were found in the Caatinga and Gliricidia sepium: 32 e 28 ufc x 10g/soil, respectively. ARDRA was as a powerful tool for the microbial community profile analysis. The Hinf I restriction enzyme disclosed that the genetic structure of the fungi 18S region in the soil under Caatinga revealed a divergent community when compared to the other treatments. The 16S region digested by the Hae III enzyme, disclosed two distinct groups: one with a 100% similarity of the bacterial genetic structure including the soils under reforested areas and under Caatinga; and the others with a 100 % of genetic similarity including the soils under the palm, pastures and Gliricidia sepium. The three parameters (microbial activity, total microbial population and the molecular profile determined by ARDRA) used in this research constituted good bioindicators, since they allowed to detect alterations influenced by different soil managements, indicating the efficiency of the agro-forestry-pasture systems for the preservation and restoration of soil in the Semi-Arid biome.